2017
DOI: 10.1002/jpln.201700277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of silver nanoparticles on the relevant soil protozoan genus Acanthamoeba

Abstract: Silver nanoparticles (AgNP) are used in a broad range of consumer products and industrial applications. During the regular product life cycle and disposal, AgNP are continuously released into the environment. Hence, the aim of this study was to investigate the potential ecotoxicological effects of AgNP exposure on amoebae. The Acanthamoeba castellanii ATCC 30234 strain and environmental isolate Acanthamoeba strain C5/2, which are both affiliated with genotype T4, were chosen as representatives of ecologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Regarding studies in Acanthamoeba, AgNPs were tested against the environmental Acanthamoeba strain ATCC 30234. In this case, the obtained results showed significant dose-dependent decrease of adherence ability and metabolic activity after 96 h of exposure (Grün et al 2017). The silver containing solutions were also examined by Willcox et al (2010).…”
Section: Discussionmentioning
confidence: 69%
“…Regarding studies in Acanthamoeba, AgNPs were tested against the environmental Acanthamoeba strain ATCC 30234. In this case, the obtained results showed significant dose-dependent decrease of adherence ability and metabolic activity after 96 h of exposure (Grün et al 2017). The silver containing solutions were also examined by Willcox et al (2010).…”
Section: Discussionmentioning
confidence: 69%
“…Further to the soil type and the AgNP functionalization, several studies documented a significant impact of the exposure time on the toxicity of AgNP in soils [16,[32][33][34]. By a statistically significant regression and correlation analysis between silver toxicity and exposure time we recently confirmed loamy soils as a sink for silver nanoparticles and their concomitant silver ions due to ageing processes of the silver species and their slow return to the biological soil system [17].…”
Section: Introductionmentioning
confidence: 73%
“…An internalization of negatively charged nanoparticles could be occured through nonspecific binding and clustering of the particles on cationic sites on the plasma membrane and subsequent endocytosis or by direct diffusion through the cell membrane [106]. Here, Ag10-COOH could act as a trojan horse: metabolization processes in food vacuoles and lysosomes allow the uncoating of AgNP and enable the direct release of Ag + ions into the cytoplasm causing intracellular damages [32,107].…”
Section: Soil Texture× Silver Speciesmentioning
confidence: 99%
“…However, despite rapid advance in nanotechnology, only a few studies on the activity of nanoparticles against Acanthamoeba spp. have been previously performed and have shown that the tested nanoparticles are well absorbed by Acanthamoeba trophozoites and decreased their adherence ability and metabolic activity [18,28,29,30]. However, the mechanism of action of AgNPs and AuNPs is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%